2011
DOI: 10.1039/c1mb05113j
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphorylation analysis in archival clinical cancer samples by shotgun and targeted proteomics approaches

Abstract: Protein phosphorylation affects most eukaryotic cellular processes and its deregulation is considered a hallmark of cancer and other diseases. Phosphoproteomics may enable monitoring of altered signaling pathways as a means of stratifying tumors and facilitating the discovery of new drugs. Unfortunately, the development of molecular tests for clinical use is constrained by the limited availability of fresh frozen, clinically annotated samples. Here we report phosphopeptide analysis in human archival formalin-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…It has been assumed that the cross-linking of proteins prevents a proteomic analysis. Recently, it could be shown that proteins can be effectively extracted from formalin-fixed and paraffin-embedded samples and that the proteins and phosphorylations are quantitatively preserved compared with fresh frozen tissues (56,61,62).…”
Section: Resultsmentioning
confidence: 99%
“…It has been assumed that the cross-linking of proteins prevents a proteomic analysis. Recently, it could be shown that proteins can be effectively extracted from formalin-fixed and paraffin-embedded samples and that the proteins and phosphorylations are quantitatively preserved compared with fresh frozen tissues (56,61,62).…”
Section: Resultsmentioning
confidence: 99%
“…tides in the assay and it is technically possible to retrieve phosphopeptides from FFPE tissues (41). However, the question remains whether this would be a reliable approach for FFPE tissues.…”
Section: Targeted Mass Spectrometry In Formalin-fixed Tissuesmentioning
confidence: 99%
“…Briefly, FFPE sections were deparaffinized in xylene and washed twice with absolute ethanol. Protein extracts from FFPE samples were prepared in 2% SDS buffer using a protocol based on heat-induced antigen retrieval (6). Protein concentration was determined using the MicroBCA Protein Assay Kit (Pierce-Thermo Scientific).…”
Section: Total Protein Preparationmentioning
confidence: 99%
“…Fresh or fresh-frozen specimens are ideal for molecular profiling but rarely available in the clinic. In recent years, we and others have demonstrated that formalinfixed, paraffin-embedded (FFPE) tissue can be readily analyzable by MS-based technologies (6,7). On the other hand, previous studies demonstrate the possibility of performing experiments to analyze the expression of miRNAs in FFPE tissues (8).…”
Section: Introductionmentioning
confidence: 99%